2008
DOI: 10.1007/s11224-008-9386-8
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the electronic structure for iridium nitride under high pressure

Abstract: We present density functionary theory (DFT) calculations on the structural parameters and electronic structure for iridium nitride by using the generalized gradient approximation (GGA) and the Perdew-BurkeErnserhof (PBE) exchange-correlation functional. The lattice parameters and bulk modulus (B 0 ) for the ground state are obtained, and the energy band structure and electron densities of states (DOS) of IrN 2 are presented. It is found that IrN 2 has a very close indirect energy gap. There is a strong covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Li et al [320] performed density functional theory calculations on the structural parameters and electronic structure of iridium nitride and presented the results in the last article of issue 6. Enthalpy of formation data is absent from experiment: however, ab initio theory has advanced our understanding of IrN both as solid [321] and as a diatomic molecule [322].…”
Section: Issuementioning
confidence: 99%
“…Li et al [320] performed density functional theory calculations on the structural parameters and electronic structure of iridium nitride and presented the results in the last article of issue 6. Enthalpy of formation data is absent from experiment: however, ab initio theory has advanced our understanding of IrN both as solid [321] and as a diatomic molecule [322].…”
Section: Issuementioning
confidence: 99%
“…Furthermore, N-rich materials boast remarkable physical properties. Iridium nitride, for instance, displays a high elastic modulus, indicating potential applications requiring structural integrity . Certain metal nitride polymorphs have also been shown to possess radiation resistance, making them interesting candidates for use in harsh environments …”
Section: Introductionmentioning
confidence: 99%
“…Iridium nitride, for instance, displays a high elastic modulus, indicating potential applications requiring structural integrity. 31 Certain metal nitride polymorphs have also been shown to possess radiation resistance, 32 making them interesting candidates for use in harsh environments. 33 Interestingly, recent studies have shown that Sr exhibits superconductivity (SC) under moderate pressure conditions.…”
Section: ■ Introductionmentioning
confidence: 99%